2023
DOI: 10.1093/clinchem/hvac209
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormone-Binding Globulin and Risk of Coronary Heart Disease in Men and Women

Abstract: Background The role of sex hormone-binding globulin (SHBG) levels in clinical risk stratification and intervention for coronary heart disease (CHD) remains uncertain. We aimed to examine whether circulating levels of SHBG are predictive of CHD risk in men and women. Methods We investigated the association between SHBG and the risk of incident CHD in 128 322 men and 135 103 women free of CHD at baseline in the prospective Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…A meta-analysis incorporating ten previous observational studies indicates that circulating SHBG levels are associated with lower CHD risk in both men and women 10 . Furthermore, the results of two recent MR studies on the same topic also support the conclusion that an increase in SHBG levels is associated with a reduced risk of CHD 10 , 44 . Our mediation analysis highlights that this biological effect of SHBG is largely achieved by improving the blood lipid profiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis incorporating ten previous observational studies indicates that circulating SHBG levels are associated with lower CHD risk in both men and women 10 . Furthermore, the results of two recent MR studies on the same topic also support the conclusion that an increase in SHBG levels is associated with a reduced risk of CHD 10 , 44 . Our mediation analysis highlights that this biological effect of SHBG is largely achieved by improving the blood lipid profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these findings need to be further verified by evidence-based medicine methods with higher level of evidence. Additionally, other studies have shown inverse association between serum SHBG levels and the risk of coronary heart disease (CHD) 10 , but the mechanism is not clear. The lipid infiltration hypothesis is currently the most widely accepted theory explaining the mechanism of atherosclerosis 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Different levels of endogenous sex hormones may partially explain the difference. In postmenopausal women, the lack of protective sex hormones may lead to an increased risk of stroke [ 9 , 12 , [20] , [21] , [22] , [23] , 26 , [35] , [36] , [37] , [38] , [39] ]. In this study, our findings demonstrate that SHBG exerts a protective effect on stroke and IS [ 12 , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] ].…”
Section: Discussionmentioning
confidence: 99%
“…SHBG is negatively related to adiposity and serum glucose and insulin, but the relationship to inflammation has not yet been clearly established 36 . Low SHBG is a risk factor for type 2 diabetes and cardiovascular disease 41 , 42 . Thus, high SHBG combined with other proteins that were elevated in the LIFE group such as adiponectin (ADIPOQ), apolipoproteins A-1, M, C-1, and D, and alpha-2-macroglobulin (A2M) are consistent with a proteomic profile linked to lowered chronic disease risk 39 , 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%